PERANAN KANTOR JASA SURVEYOR KADASTER BERLISENSI (KJSKB) DALAM PELAKSANAAN PENDAFTARAN TANAH SISTEMATIS LENGKAP (Studi Kasus di Kantor Pertanahan Kabupaten Karanganyar) - ZAENURI, ACHMAD (Dinamika Hukum, 2019)
The objectives of this study are: to examine the existence of Licensed Cadastre Surveyor Service Office (KJSKB) on the implementation of Complete Systematic Registration in Karanganyar Regency to find out KJSKB's legal authority in PTSL implementation in Karanganyar Regency. The approach method used in this study is juridical normative. The nature of the research used in this study is descriptive analytical. The results of the study show that the role of Licensed Cadastre Surveyor Service Office (KJSKB) in the implementation of Complete Systematic Land Registration in Karanganyar in the field of surveying, measuring and mapping land was not optimal yet. The survey, measurement and mapping activities which are carried out by KJSKB include: Planning, Making Working Maps, Measuring and Determining the Limits of Land Plots, Making Measuring Images, Mapping Fields of Lands, Cluster Identification 4, Printing Field Maps and Reporting. Lessoptimal planning causes longer work completion times. It impacts on the next stage. Ignoring local wisdom impacts on non-optimal of obtaining data. Making Nonstandard Measuring Images results in the rejection of the quality control process by the BPN Team. The measuring staff experience that is lacking in field mastery also has an impact on less than optimal results. The KJSKB legal authority in the implementation of PTSL in Karanganyar Regency is related to the work of land registration is the data of the size of the field, Measure Image, Map of Land Affairs, and the results of services or other survey and mapping activities in accordance with the provisions of legislation. Systematic Land Registration Complete in principle to map and register land in full. The limitation of KJSKB's authority in accessing KKP application data has an impact on the results of work that is not optimal. In planning and making work maps are not given maximum access. The authority to sign the Letter of Measure is still the domain or authority of the deputy chairperson of the physical task force Keywords: licensed cadastral surveyor, systematic land registration, delegation of authority.